Nolo's patents for beginners - Pressman, David, 1937-; Stim, Richard (Nolo, 2024)
Provides an introduction to the patenting process, with everything you need to know about patent law basics, including the latest implications of the America Invents Act, the most important change to American patent law in two centuries. Includes patent and invention resources and a glossary of patent terms. --Adapted from publisher description.